DCFTA Implementation: Opportunities and Challenges for Ukrainian Entrepreneurs - Oleksandr KUBATKO; Tetyana PIMONENKO (Eastern European Journal of Regional Studies)
The paper deals with the analysis of Ukrainian entrepreneurs readiness for implementation of Deep and Comprehensive Free Trade Area (DCFTA). The authors analyzed the ongoing condition for running business in Ukraine, and results were in favor negative industrial business tendencies combined with macroeconomic instability. Moreover, the military confrontation in the East of Ukraine has had negative consequences for the social, moral and economic situation in the country. Authors have estimated the chances and goals of Ukrainian entrepreneurs to be achieved using the DCFTA. Thus, the effect of DCFTA implementation could provide 6 % of the additional GDP in the medium term. The share of export to EU in total Ukrainian export of goods and services has increased from 26.7 % in 2013 to 32.8 % in 2015. The entrepreneurs of agriculture sector and textile industry are expected to receive the most positive effect of DCFTA implementation. Thus, the export of the cereal crops has increased by 3 % in 2015 compare with 2013. In addition, the export of Electrical machinery and equipment also has increased by 3% in 2015 comparing to 2013. Moreover, DCFTA implementation allowed opening new boundaries and opportunities for entrepreneurs in IT sector. At the same time, the machine building industry is expected to be very sensitive to the DCFTA implementation due the low competitiveness.